Studying Natural Science in Elementary School Using NOS-Oriented Cooperative Learning Model with the NHT Type (Jurnal Pendidikan IPA Indonesia, 2018)
Elementary school students’ achievement in natural science in the academic year of 2015/2016 at Cluster V, Buleleng regency, Bali province was considerably low. An early observation also revealed low motivation, negative attitudes towards teachers, low self-esteem and low confidence in self-capability. Therefore, a breakthrough approach was urgently required to improve the students' performance in natural science learning. The current article aimed at investigating the effects of the (Nature of Science) NOS-oriented cooperative learning model with the Numbered Head Together (NHT) on the elementary school students’ achievement in natural science. The study was a quasi-experimental research adopting the post-test only control group design. The research conducted in elementary schools in Cluster V Buleleng sub-district, Buleleng regency, Bali, Indonesia. The research subject was 137 students in Grade 5 consisting of six classes from  5 elementary schools. The hypothesis was examined using an inferential statistics, the t-test. The results showed that there was a significant difference in the learning results of natural science between the students taught with the NOS-oriented cooperative learning model with the NHT type and those with the conventional learning model (t count = 7,048 t table = 2,000). The students taught with the NOS-oriented constructive learning model with the NHT type achieved better than those with the conventional learning model. Therefore, it concluded that the NOS-oriented cooperative learning model with the NHT type gave positive effects on the fifth year students’ achievement in natural science learning.